Leaving the tropics: The successful colonization of cold temperate regions by Dolicheremaeus dorni (Acari, Oribatida). (23rd March 2018) - Schäffer, Sylvia; Stabentheiner, Edith; Shimano, Satoshi; Pfingstl, Tobias
Abstract: Species diversity is generally higher in the tropics compared to the temperate zones. The phenomenon that one species of an almost exclusively tropical living genus was able to adapt successfully to the cold northern regions is rather rare. However, the oribatid mite Dolicheremaeus dorni represents such a species and is in the focus of this study. While 180 Dolicheremaeus species are confined to the tropics and subtropics, only five species are known to occur in temperate climates and D. dorni represents the only species with a wider distribution in this climatic region. This species is distributed in Central and Southern Europe and was now recorded for the first time in Austria. A morphological and molecular genetic investigation of specimens from Austria, Poland and Croatia confirmed this distribution pattern and revealed specific geographic clades and haplotypes for each population and hence indicate low gene flow between populations. A further molecular genetic analysis of the 18S rRNA gene sequence of D. dorni confirmed its phylogenetic position within Carabodoidea. Based on record information, this species is associated with trees or tree habitats and seems to be rather a generalist than a specialist for a specific substrate (e.g., tree species) or food source. Abstract : The oribatid mite genus Dolicheremaeus represents a very diverse taxon that predominantly occurs in the subtropics and tropics. Dolicheremaeus dorni is one of very few species that has managed to colonize temperate habitats. This species is associated with trees or tree habitats and is a generalist feeder. A morphological and molecular genetic investigation confirmed the distribution of this species in Central and Southern Europe and revealed specific geographic clades and haplotypes for each population indicating low gene flow between populations.